PENINGKATAN KUALITAS KEPUASAN PELANGGAN MELALUI STRATEGI PROMOSI DAN KUALITAS PELAYANAN DI PT. LMI - Bambang Fajarisman (Universitas Prof. Dr. Moestopo (Beragama), 2021)
This study aims to find the dominant factors that influence the level of customer satisfaction at PT. LMI. The level of customer satisfaction is an absolute goal that must be achieved by every business organization. Customer satisfaction is the main trigger in moving business organizations by optimizing sales and business process mechanisms. Customers who get satisfaction of goods or services from a company will have an impact on repurchase intention. If the factors that influence customer satisfaction can be identified, the level of customer satisfaction can be measured, assessed, and planned for business activities. This research uses quantitative methods. The population used is 360 respondents who are active members of PT. LMI. The number of samples used and can represent the population is as many as 186 respondents. Sampling using random sampling technique. The data analysis method uses regression analysis and the results of this study state as follows, 1) the promotion strategy has a positive effect on customer satisfaction by 30.6%. 2) service quality has a positive effect on customer satisfaction by 59.3%. 3) simultaneously the promotion strategy and service quality have a significant effect of 70.6% on customer satisfaction.